A diagnostic and management odyssey of a rare case of rhizomelic chondrodysplasia punctata - Qurat Ul Ain; Halim, Alia; Shabbir , Asma; Marriam, Amina (Journal of the Pakistan Medical Association, 2025)
Rhizomelic chondrodysplasia punctata (RCDP) is one of the rare inherited peroxisomal disorders that belongs to the heterogeneous group of chondrodysplasias presenting with proximal shortening of the limbs and distinctive punctate calcifications of bones and cartilages. This disorder occurs due to mutations in the genes responsible for peroxisomal biosynthesis inherited commonly as autosomal recessive, though a few are reported as x-linked dominant and recessive. The diagnosis can be made on clinical findings along with a skeletal survey; however, sonography and genetic analysis are crucial for a definitive prenatal diagnosis in cases where RCDP is inherited within a family as there is no definitive cure for RCDP and the treatment revolves around the management of its manifestations and complications. We hereby report the case of a neonate with features of RCDP. Significant respiratory involvement in RCDP babies is linked with high mortality which was also observed in this case. Key Words: Rhizomelia, Chondrodysplasia punctata, Peroxisomal disorder, Skeletal dysplasia.